Hipóxia intermitente durante o período pós-natal e mecanismos epigenéticos: implicações a longo prazo na ventilação pulmonar e no padrão motor respiratório - Bittencourt-Silva, Paloma Graziele (2019)
During the postnatal period, the respiratory network undergoes through developmental and maturational processes that are critical for the proper functioning of central mechanisms that controls breathing. Periods of apnea are commonly observed in preterm infants and it is suggested to be an important risk factor for the development of cardiorespiratory diseases in adults. In this study, we investigated the changes in pulmonary ventilation and respiratory motor outputs of juvenile and adult rats exposed to post-natal intermittent chronic hypoxia (pCIH), as well as the participation of DNA methylation processes in the induction of these alterations. To reach these goals, newborn rats (P1) were exposed to pCIH [6% O2 for 30 s every 10 min, 8 hours per day (9:30 - 5:30)] during the first 10 days of life, whereas control animals were maintained in normoxia. Injections of decitabine (DNA methylation inhibitor, 1 mg/kg, i.p.) or vehicle were performed on days P1, P4, P7 and P10. After this period, the animals were kept in normoxia until the day of the experiments. When young, pCIH animals presented, under basal conditions, increased tidal volume and minute ventilation, associated with irregularities in the respiratory frequency. Decerebrated, artificially perfused in situ preparations of pCIH rats exhibited, at resting conditions, an increase in phrenic burst amplitude associated with reduced vagal efferent activity. No significant differences were observed in HN activity. The in situ preparations of pCIH animals also presented higher apneic threshold and lower sensitivity to hypercapnia at 7% CO2, but not at 10% CO2. The respiratory responses to stimulation of carotid body chemoreceptors with KCN in the pCIH in situ preparations were similar to controls. In adulthood, pCIH rats also exhibited increased tidal volume and irregularities in the respiratory frequency. Inhibition of DNA methylation during pCIH prevented the changes in pulmonary ventilation and respiratory motor activity of juvenile rats, as well as the modifications in pulmonary ventilation of adult rats. We therefore conclude that the exposure to intermittent hypoxia during the postnatal period modifies the functioning of the respiratory network and promotes persistent changes in respiratory pattern and pulmonary ventilation. Intermittent hypoxia, observed in the apnea of prematurity, may be a relevant factor predisposing to respiratory pathologies in adults, such as obstructive sleep apnea. We conclude that epigenetic mechanisms, such as DNA methylation, actively promote and sustain the changes induced by pCIH.